REKAYASA PENGONTROLAN KEAMANAN SEPEDA MOTOR INVENTARIS MELALUI MEDIA HANDPHONE PADA PT. KMK GLOBAL SPORT - Djoko Soetarno; Haryanto Haryanto; Andry Bastian (Universitas Raharja, 2016)
In a company that has an inventory of vehicles ( Motorcycles ) terkandang appears constraints on system security and system control, because security officer ( guard ) must control one by one manually motorcycle . There are several systems that can be tailored to these problems , one of which is the control system automatically uses the Bluetooth facility . In this system using Bluetooth facility to give commands to the microcontroller used , ie ATmega328 -based ArduinoUno . Security guard simply open the application Bluetooth Controller and connect the Android smartphone to Bluetooth which is mounted on the motorcycle inventory , and then press